The Gender Inequalities Index (GII) as a New Way to Understand Gender Inequality Issues in Developing Countries - Gaëlle Ferrant (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
The measurement of gender inequalities has become an important topic in the academic literature. First, appropriate indicators are needed to compare the relative situation of women in developing countries. Second, there is renewed attention given to the relationship between gender inequality and economic growth. Measuring gender inequalities contributes to knowing whether greater inequality promotes or hampers growth. The aim of this paper is twofold. First, the Gender Inequalities Index (GII) is built through a new methodology using Multiple Correspondence Analysis (MCA), which determines endogenously the weight of each variable. The GII avoids comparison between countries and ranking. Second, the GII is used to study the relationship between gender inequalities and economic growth using seemingly unrelated regressions. Results show large variations between regions: South Asia has the worst score with an average of 0.63, Sub-Saharan Africa and Middle East and North Africa follow with an average of 0.48 and 0.46 respectively. These situations lead to reducing the potential growth rate by 4% in South Asia and 3% in Sub-Saharan Africa and Middle East and North Africa countries.
Keywords: J16; O11; O57; C43; 330; Composite index; gender inequality; development economics